Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil - Costa, Wilson J.e.m.; Brasil, Gilberto C. (Zootaxa, 2004)
Simpsonichthys radiosus, new species, from the upper Rio Tocantins basin, central Brazil, is described. It belongs to a clade herein denominated Simpsonichthys notatus species group, which includes S. notatus, S. stellatus, S. similis, S. rufus, S. trilineatus, S. auratus, and S. ocellatus, and is diagnosed by a unique pattern of frontal squamation. The new species is distinguished from other species of the S. notatus group by possessing a wider basihyal and a unique color pattern on the caudal fin in males, consisting of light blue stripes parallel to the fin rays alternating with subdistal blue spots. A key to the species of the S. notatus group is provided.